Anthelmintic activity of Stevia aristata extract on Echinococcus granulosus: in vitro and in vivo study - Albani, Clara Maria (2021)
Cystic echinococcosis (CE) is a worldwide zoonotic disease caused by Echinococcus granulosus, which produces long-term infections in humans and animals. Available anti-parasitic treatment against CE is mostly limited to the use of benzimidazoles, mainly albendazole (ABZ). However, it has undesirable side effects and their efficacy is about 50%. Based on the problematic described, new treatment alternatives are urgently needed. Plants from the Stevia genus (Asteraceae) are a potential source of anti-protozoal and anti-microbial compounds. The aim of the present study was to evaluate the in vitro and in vivo efficacy of the Stevia aristata dichloromethane extract against E. granulosus. Viable and free protoscoleces or cysts were treated with 100, 50, 10 and 5 μg/ml of the extract. Viability assessment using the methylene blue exclusion test and scanning electron microscopy (SEM) (for protoscoleces) or evaluation of germinal layer collapse (for cysts) was performed. CF-1 mice (n=30) infected with E. granulosus were allocated into the following experimental groups (6 months post-infection): (1) Control, (2) ABZ 25 mg/kg, every 24 h for 30 days; (3) S. aristata 50 mg/kg, every 24 h for 23 days. At the end of the treatment the weight of the cysts was recorded and samples were analysed by SEM. Protoscoleces viability decreased quickly with 100 µg/ml, reaching 0% after 20 days of treatment. After 4 days of incubation, the collapse of the germinal layer was observed in 60 ± 5.8% and 83.3 ± 12.0% of cysts treated with 50 and 100 µg/ml, respectively. Whilst ultrastructural damage was observed in the cysts obtained from S. aristata or ABZ treated mice, no significant differences in the weight of the cysts were obtained (P > 0.05). In conclusion, S. aristata treatment caused high protoscolicidal and cysticidal effects, but not significant reduction in the weight of the cysts in experimentally infected mice.